(untitled) - Hashemi, Louise (Cambridge, 2010)
Objective PET Second edition is a completely updated and revised edition of the best-selling Objective PET course. This edition includes great new features, including brand new 'Corpus spots' alerting students to common mistakes by PET candidates. The Student's Book includes a CD-ROM for extra language practice, including one complete printable PET practice test. The accompanying website includes an additional printable PET practice test. A Student's
Keywords: English language,Ngôn ngữu Anh